Konsumsi dan kecernaan bahan kering dan bahan organik sapi bali penggemukan pola peternak yang di suplementasi pakan komplit berbasis silase batang pisang - Syawaludin Lama Wuran; Sukawaty Fattah; Yohanis Umbu Laiya Sobang (Jurnal Peternakan Lahan Kering, 2019)
This study aimed at evaluating the effect of feeding oncomplete feed containing fermented banana stem silage on feed intake, and the digestibility of dry matter and organic matter of fattening Bali cattlefeeding as usually practiced by local (Timorese) farmers. Experimental animals employed in this research were 9 heads of growing male Bali cattleof 1 to 1.5 years old with the body weight ranging from 111 to 136kg with an average of 120.79kg and coefficient variation (CV) 5.72%, were employed. The experimental design used was completely randomized design consisted of 3 treatments and 3 replications. Those treatments were T0:feedas usually offered by the local farmers (leaves of Leucaenaleucocephala, Acacia leucophloea and Ficussp.) + 1kg complete feed without fermented banana stem silage added, T1: feed as usually offered by the local farmers + 1kg complete feed added with 10% fermented banana stem silage, and T2:feed as usually offered by the local farmers + 1kg complete feed added with 20% fermented banana stem silage. Data collected was subjected to Analysis of Variance (ANOVA). The results showed that there was a significance effect (P<0.05) of treatments on both thedigestibility of dry matter and organic matter,but there was no significance effect (P>0.05) of treatments found on both the intake of dry matter and organic matter. In conclusion, fed on complete feed with the addition of fermented banana stem silage was significantly affected the digestibility of both dry matter and organic matter, but not on the intake of both dry matter and organic matter.